Tekst dzieła literackiego jako partytura - Martuszewska, Anna (Wydawnictwo Naukowe UAM, 2005)
The point of departure for the author of this article is a brief presentation of Bolesław Prus' unpublished notes on the subject of relations of music and literature, stimulating the latter's interest in this subject. Then the author presents an interpretation of a musical score by Roman Ingarden and later juxtaposes similarities and differences between the score of a work of music with the graphic notation of the text of a literary work (what is most important here is the potential existence of sound in the graphic notation). The article ends with a suggestion that the possibility of comparing results from the kinship or even kinship of both arts.
The text of a literary work as a score